Differences between 48 and 72-hour intervals on match load and subsequent recovery: a report from the Brazilian under-20 national football team - Wilke, Carolina Franco; Coimbra, Cândido Celso; Drummond, Filipe R.; Drummond, Lucas Rios; Campos, Helton Oliveira; Kanope, Tane; Ramos, Guilherme Passos (Frontiers in Sports and Active Living, 2024)
Purpose To compare the external and internal load and subsequent recovery of football players after international tournament matches separated by 48 h vs. 72 h. Methods A total of 14 male football players from the Brazilian National Team, competing in the 2019 South American Under-20 Championship, participated in the study. Match load was quantified using GPS variables and perceived exertion ratings (1). Additionally, before and 13–15 h after each match, players answered questions about the number of hours and quality of sleep, recovery status, and muscle soreness (0–10) and provided a blood sample for creatine kinase and reactive C-protein analysis. Values of all variables were compared between matches played with 48-h intervals (matches 1–4) and 72-h intervals (matches 5–8). Results No significant differences in performance or perceptual parameters were observed between matches (p = 0.136–0.953). However, CK was higher in matches 1–4 compared to matches 5 and 6; and ΔPCR was higher in matches 2 and 3 compared to matches 5 and 6, and in match 4 compared to matches 5 and 8. Conclusions After matches with a 48-h rest interval, players showed increased markers of inflammation and muscle damage compared to matches with a 72-h rest interval.